Synthesis, Crystal Structure and Antibacterial Activity of Ca(II) Complex with 2-(Phenylsulfonamido)acetic Acid - Xi-Shi, Tai; Si-Yuan, Chu; Chun-Ying, Tang (Asian Journal of Chemistry, 2012)
A new ligand 2-(phenylsulfonamido)acetic acid (L) and its Ca(II) complex have been synthesized and characterized by elemental analysis, IR spectroscopy and single-crystal X-ray diffraction. The results showed that the complex formed one dimensional chained structure through intramolecule and intermolecule hydrogen bonds and p-p stacking. The antibacterial assay of the Ca(II) complex and the lignd L was tested using a modified version of 2-fold serial dilution method. The Ca(II) complex shows considerable antibacterial activity against Escherichia coli, Bacillus subtilis and Staphylococcus white.